Pengaruh QRIS Dalam Peningkatan UMKM Sektor Kriya di Kota Bekasi - Mohammad Haddad Bayhaqi; Anita Maulina (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract.This research analyzes the effectiveness of the Quick Response Code Indonesian Standard (QRIS)in enhancing Micro, Small, and Medium Enterprises (MSMEs), specifically in the craft sector in BekasiCity. Using a qualitative descriptive approach, this study collects data through in-depth interviews,observations, and documentation. The analysis is based on the Technology Acceptance Model(TAM), highlighting perceived usefulness, satisfaction, and risks. The findings show QRIS improvestransaction efficiency and market reach, while satisfaction sustains its usage. However, constraintssuch as network instability and MDR fees hinder optimal adoption. The study concludes QRIS iseffective, but requires ongoing education and support.Keywords: Bekasi City, Craft Sector, Digital Payment, QRIS, TAM, UMKM